Evieta-Based Learning Material in English Business Class: Students’ Perceptions: (Study Case Taken From Vocational School – IPB University) - Irma Rasita Gloria Barus; Marudut Bernadtua Simanjuntak (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2020)
The purpose of this study is to test students' perceptions of using Evieta-based learning in Business English classes at the Vocational School - IPB University, Bogor. The study was prepared by lecturers as authors of the article for the multimedia learning system used. The data comes from questionnaires on how students perceive implemented learning using the Likert scale. The scoring system performed recommended and non-recommended points. The data were analyzed descriptively using a scoring table from 1 to 100, which is intended to represent the students' views or opinions. The results of this study, which focus on study materials for the English Business class, show that there is a consensus among students that this learning-based learning is effective when applied and applied. The average perception score is 87, indicating six elements of the product (comfort, content, efficient use, language, clarity, and enjoyment).